THE EFFECTIVE USE OF ACTIVE METHODOLOGIES IN TEACHING ACTIVITIES - Dalva da Silva Santos, Maria; Batista Leonez, Erasmo; Dantas Santos Costa, Josilene; Santana de Souza, Tiago; Nayara Ferreira de Souza Bezerra, Ítala (Revista Gênero e Interdisciplinaridade, 2025)
This article studied the integration of active methodologies in teaching activities. As such, the problem aimed to determine to what extent active methodologies can be adapted to different educational contexts and levels of teaching. Aware of this, the main objective was to analyze the effective use of active methodologies in teaching activities, focusing on problem-based learning, project-based learning, and flipped classroom. As a methodology, a qualitative literature review was explored. In the results, it was observed that the application of active methodologies has shown significant improvements in the understanding and retention of content, as well as the development of essential skills for the 21st century, such as critical thinking, autonomy, and problem-solving ability. These methodologies have the potential to be adapted to various educational contexts, from early childhood education to higher education. A suggestion for future research is to further investigate the specific challenges faced in the adaptation of active methodologies, such as educators’ resistance to change, lack of material resources, and insufficient institutional support.